Effect of Extracts from Zygophyllum Fabago on Growth and Activity of Candida Albicans and Aspergillus Flavus - Ali, B. Z.; AL- Qaisi, E. E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study was conducted to evaluate the anti fungal activity of water and alcohol ic extracts (cold and hot) and the crude alkaloid extracts of leaves, seeds and roots of Zygophyllum fabago plant against a standard isolate of C. albicans and an isolate of A. jlavus which was proved to produce aflatoxins. Investigation of presence of active antimicrobial compounds in this plant parts was carried out, crude al kaloid extract was also separated using TLC technique. The antifungal activity of all these extracts was estimated against the two fungi. Results showed variation in anti fungal activity of different extracts against C. albicans, where the MIC values of the water extracts (cold and hot) and the alcoholic extracts (cold and hot) from leaves was (50) mg/ml, (50,40,30,20) mg!ml from seeds and (50, 40, 60,60) mg/ml from root, respectively, Whereas the MIC of the crude alkaloid extracts from leaves, seeds and roots were (40,50,50) mg/ml respectively which indicate a higher antifungal activity of the crude alkaloid extract from leaves followed by the same extract from roots then seeds. Additionally, crude alkaloid extracts showed complete inhibition of spores germination of A. jlavus at concentrations (60,70,80)mg/m l, whereas other lower concentrations delayed spores germination. Various concentrations of seeds alkaloid extracts also inhibit surface growth of A. jlavus colonies at (60,70) mg/ml. Bioautography of seeds alkaloid extracts using TLC technique revealed the presence of here compounds in the extract, these compounds showed a different inhibitory activity on the growth of A. jlavus.